A multi-objective optimization approach for clean treatment of food waste from an economic-environmental-social perspective: A case study from China. (10th July 2022) - Deng, Yawen; Chen, Xingyu; Adam, N.G. Tsan Sheng; Xu, Jiuping
Abstract: The combination of anaerobic digestion and transesterification technologies to treat food waste avoids the environmental problems associated with other treatment methods and effectively utilizes food waste to produce valuable products for society. However, as the anaerobic mono-digestion of food waste is not as efficient as anaerobic co-digestion of food waste with other substrates, this needs to be considered in food waste treatment system planning. Few studies on the mixed treatment of food waste with other substrates have considered the system from the economic, environmental, and social perspectives. Therefore, this paper comprehensively considered the economic, environmental, and social objectives of food waste treatment systems and developed a multi-objective optimization model to investigate the optimal systems operational strategy for food waste mixed treatment with other substrates by anaerobic co-digestion and transesterification. Uncertainties regarding the source quantities of food waste and substrates are solved in the proposed model using trapezoidal fuzzy numbers, and a case study in China is given to assess the validity and practicality of the proposed model. It was found that different substrate types and different mixing proportions affected the optimal system decisions, environmental and economic objectives were mutually constraining, and there was a positive relationship between the social objectives and the economic and environmental objectives.